PERANCANGAN UI/UX APLIKASI WEDDING ORGANIZER WILAYAH SURABAYA MENGGUNAKAN METODE USER CENTERED DESIGN - Nissa Adwitiya Aji; Dwi Teguh Imanto (CV. Adiba Aisha Amira, 2026)
There are numerous things to consider when arranging a wedding. To solve this problem, people often choose to use wedding organizer services. However, some wedding organizer service companies still do conventional marketing, making it difficult for prospective brides to find the best vendors at the right price. The reason for this investigation is to form an interface with the User Centered Design strategy, an application plan that can get its client needs ideally. Through the stages of the method, the design that has been designed through prototypes is carried out using usability testing which is measured based on three aspects, namely effectiveness, efficiency, satisfaction. The comes about of the SUS calculation over-gets the ultimate result with a normal score of 79.25, which esteem is categorized as acceptable (good) or produces a plan with great ease of use.